China's great migration: the impact of the reduction in trade policy uncertainty - Facchini, Giovanni; Liu, Maggie Y.; Mayda, Anna Maria; Zhou, Minghai (Unpublished, 2017)
We analyze the effect of China's integration into the world economy on workers in the country and show that one important channel of impact has been internal migration. Specifically, we study the changes in internal migration rates triggered by the reduction in trade policy uncertainty faced by Chinese exporters in the U.S. This reduction is characterized by plausibly exogenous variation across sectors, which we use to construct a local measure of treatment, at the level of a Chinese prefecture, following Bartik (1991). This allows us to estimate a difference-in-difference empirical specification based on variation across Chinese prefectures before and after 2001. We find that prefectures facing the average decline in trade policy uncertainty experience an 18 percent increase in their internal in-migration rate this result is driven by migrants who are "non-hukou", skilled, and in their prime working age. Finally, in those prefectures, working hours of "native" unskilled workers significantly increase - while the employment rates of neither native workers nor internal migrants change.